The Effect of Ticagrelor on Platelet Reactivity in Patients with Clopidogrel Resistance Undergoing Neuroendovascular Procedures. Issue 3 (17th April 2020) - Qureshi, Adnan Iqbal; Jahngir, Muhammad Umair; Qualls, Kathryn; Akinci, Yasemin; Lobanova, Iryna; Liaqat, Jahanzeb; Gao, Xiaoyu; Akhtar, Iqra Naveed; Kraus, Jacqueline; Uzun, Guven; French, Brandi; Siddiq, Farhan; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Suboptimal platelet inhibition by clopidogrel (clopidogrel resistance) may be associated with high rates of stent thrombosis and ischemic events. Our objective was to determine if ticagrelor, a P2Y12 receptor inhibitor, can result in platelet inhibition in patients with clopidogrel resistance. METHODS: A thromboelastography‐platelet mapping assay was used in all patients undergoing neuroendovascular procedures requiring oral clopidogrel. In patients with suboptimal platelet inhibition (<60%) on clopidogrel, ticagrelor was imitated after an oral bolus of 180 mg followed by 90 mg twice daily and the platelet mapping assay was repeated. The primary endpoint was hemorrhagic complications classified as major (hemoglobin decrease >5 g/dL or intracranial hemorrhage with deficits), minor (hemoglobin decrease 3‐5 g/dL or intracranial hemorrhage without residual deficits), or insignificant. RESULTS: Suboptimal platelet inhibition on clopidogrel was seen in 70 of 106 patients undergoing neuroendovascular procedures. There was a significantly higher magnitude of platelet inhibition with ticagrelor compared with clopidogrel in patients with clopidogrel resistance (mean ± SD: 85.90 ± 10.74% vs. 29.26 ± 17.71%; P < .001); 50 of 70 patients showed optimal inhibition. Two patients had major (fatal) hemorrhagic events (both received either intravenous thrombolytics and/or eptifibatide infusion). Three patients had minor hemorrhagic events, and two patients had insignificant hemorrhagic events. Four of seven hemorrhagic events occurred in patients with optimal response to clopidogrel, two occurred in patients with suboptimal response to ticagrelor, and one occurred in a patient with optimal response to ticagrelor. CONCLUSIONS: Oral ticagrelor can augment platelet inhibition in patients who have clopidogrel resistance.